2015
DOI: 10.1111/jopy.12169
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Judgments of Social Desirability

Abstract: This study evaluates sex differences in the perceived desirability of personality behaviors and beliefs. Men and women (N = 149, Mage  = 18.7) judged the social desirability scale values (SDSVs) of 150 personality statements as applied either to a male target or a female target. For comparison, some estimated SDSVs with no target sex specified. A separate sample of 537 respondents endorsed the 150 items via self-report. Raters showed a high consensus in their SDSV judgments within conditions (α = .86 to .90) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Experts could judge the social desirability of specific answers to questions and develop an index of each subject’s socially desirable responses (Konstabel, Aavik, & Allik, 2006). Because of potential gender differences in socially desirable responding, items should be assessed from the perspective of both genders (Paunonen, 2016). Measuring the time used to answer each question may help identify biased responses because when people give socially desirable responses, they tend to spend less time and effort (Gamberini et al, 2014; Kaminska & Foulsham, 2013, 2016).…”
Section: Options To Address Sdbmentioning
confidence: 99%
“…Experts could judge the social desirability of specific answers to questions and develop an index of each subject’s socially desirable responses (Konstabel, Aavik, & Allik, 2006). Because of potential gender differences in socially desirable responding, items should be assessed from the perspective of both genders (Paunonen, 2016). Measuring the time used to answer each question may help identify biased responses because when people give socially desirable responses, they tend to spend less time and effort (Gamberini et al, 2014; Kaminska & Foulsham, 2013, 2016).…”
Section: Options To Address Sdbmentioning
confidence: 99%
“…Previous research from non-political fields found greater social desirability bias among women than among men (Chung & Monroe, 2003;Dalton & Ortegren, 2011;Hebert et al, 1997;Paunonen, 2016). Suppose this is also the case for political surveys.…”
Section: Election 2021mentioning
confidence: 84%
“…In Germany, for example, people more often vote for the radical right-wing AfD than they admit in surveys (Gschwend et al, 2018). If the degree or direction of social desirability bias differs between women and men (Hebert et al, 1997;Johann et al, 2016;Paunonen, 2016), this may bias estimates of gender gaps. To summarize, my study thus calculates gender gaps that are free from such bias and, by comparing real ballots to surveys, further tests whether survey data are generally suitable for studying political gender gaps.…”
Section: Introductionmentioning
confidence: 99%
“…However, measures such as methadone dose and duration on MMT were self-reported, allowing for a potential of social desirability bias, where participants might provide false information in lieu of more accurate responses that might be viewed as less desirable. Social desirability bias could also have elicited differing responses within males and females as behaviours might seem more desirable in one sex but not the other [ 39 ]. In addition, the findings might be affected by volunteer bias, wherein the sample recruited could not have been representative of the entire OUD population receiving treatment.…”
Section: Methodsmentioning
confidence: 99%